Solar Carbo-Thermal and Methano-Thermal Reduction of MgO and ZnO for Metallic Powder and Syngas Production by Green Extractive Metallurgy - Srirat Chuayboon; Stéphane Abanades (Processes, 2022)
The solar carbo-thermal and methano-thermal reduction of both MgO and ZnO were performed in a flexible solar reactor operated at low pressure through both batch and continuous operations. The pyro-metallurgical process is an attractive sustainable pathway to convert and store concentrated solar energy into high-value metal commodities and fuels. Substituting fossil fuel combustion with solar energy when providing high-temperature process heat is a relevant option for green extractive metallurgy. In this study, a thermodynamic equilibrium analysis was first performed to compare the thermochemical reduction of MgO and ZnO with solid carbon or gaseous methane, and to determine the product distribution as a function of the operating conditions. The carbo-thermal and methano-thermal reduction of the MgO and ZnO volatile oxides was then experimentally assessed and compared using a directly irradiated cavity-type solar reactor under different operating conditions, varying the type of carbon-based reducing agent (either solid carbon or methane), temperature (in the range 765–1167 °C for ZnO and 991–1550 °C for MgO), total pressure (including both reduced 0.10–0.15 bar and atmospheric ~0.90 bar pressures), and processing mode (batch and continuous operations). The carbo-thermal and methano-thermal reduction reactions yielded gaseous metal species (Mg and Zn) which were recovered at the reactor outlet as fine and reactive metal powders. Reducing the total pressure favored the conversion of both MgO and ZnO and increased the yields of Mg and Zn. However, a decrease in the total pressure also promoted CO2 production because of a shortened gas residence time, especially in the case of ZnO reduction, whereas CO2 formation was negligible in the case of MgO reduction, whatever the conditions. Continuous reactant co-feeding (corresponding to the mixture of metal oxide and carbon or methane) was also performed during the solar reactor operation, revealing an increase in both gas production yields and reaction extent while increasing the reactant feeding rate. The type of carbon reducer influenced the reaction extent, since a higher conversion of both MgO and ZnO was reached when using carbon with a highly available specific surface area for the reactions. The continuous solar process yielded high-purity magnesium and zinc content in the solar-produced metallic powders, thus confirming the reliability, flexibility, and robustness of the solar reactor and demonstrating a promising solar metallurgical process for the clean conversion of both metal oxides and concentrated solar light to value-added chemicals.
Keywords: Chemical Looping and Thermochemical Processes; Catalysts for Methane Reforming; Carbon Dioxide Capture Technologies